Constructing Religious Literacy through Qur’an-Based Contextual Learning and Meaning-Making for Value Internalization in Elementary Education - Donny Khoirul Azis; Irfan Musonif; Saifudin; Minan Ainur Fatah; Mahin Anas Ramadona (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
Religious literacy in Islamic education is frequently reduced to the cognitive ability to read and understand sacred texts, overlooking how meaning is constructed and enacted in lived contexts. This study investigates how Qur’an-based contextual learning shapes the development of religious literacy among elementary school students. Using an interpretive qualitative single-case study design, the research was conducted in an Indonesian elementary school through classroom observations, in-depth interviews, and document analysis. Data were analyzed using reflexive thematic analysis. The findings reveal that religious literacy is constituted through the interplay of pedagogical practices, meaning-making processes, and value internalization. First, teacher-centered and textual-oriented instruction constrains students’ opportunities for interpretive engagement, resulting in superficial and reproductive understanding. Second, meaning-making emerges through contextual mediation, where students connect Qur’anic values with their lived experiences through interaction and dialogue. Third, value internalization is a gradual, non-linear, and context-dependent process shaped by situational factors and sustained engagement. This study advances a process-oriented conceptualization of religious literacy as an interpretive and interactionally constructed phenomenon rather than a purely cognitive skill. It underscores the need to transform classroom interaction and integrate contextual learning to support meaningful understanding and the enactment of values in Islamic education.